1999
DOI: 10.1073/pnas.96.22.12965
|View full text |Cite
|
Sign up to set email alerts
|

Low-status monkeys “play dumb” when learning in mixed social groups

Abstract: Many primates, including humans, live in complex hierarchical societies where social context and status affect daily life. Nevertheless, primate learning studies typically test single animals in limited laboratory settings where the important effects of social interactions and relationships cannot be studied. To investigate the impact of sociality on associative learning, we compared the individual performances of group-tested rhesus monkeys (Macaca mulatta) across various social contexts. We used a traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
99
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 24 publications
7
99
1
Order By: Relevance
“…Humphrey (1976) hypothesized that 'intellectual prowess' would be correlated with 'social success'. However, the few studies that have addressed this hypothesis in gregarious species by testing individuals outside the wholegroup context suggested that subordinate and dominant rhesus macaques have similar capacities to learn (Drea & Wallen 1999) and that subordinate longtailed macaques are superior learners . Furthermore, in the latter studies, changes in individuals' social ranks were frequent and followed by changes in performance on the individual learning task; a drop in an animal's relative rank was accompanied by improved performance relative to the rest of the group, and a rise by poorer performance, leading the authors to assert that there did not seem to exist an 'inherent negative relationship between some hypothetical generalized learning ability and social rank' (Bunnell & Perkins 1980, page 522).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Humphrey (1976) hypothesized that 'intellectual prowess' would be correlated with 'social success'. However, the few studies that have addressed this hypothesis in gregarious species by testing individuals outside the wholegroup context suggested that subordinate and dominant rhesus macaques have similar capacities to learn (Drea & Wallen 1999) and that subordinate longtailed macaques are superior learners . Furthermore, in the latter studies, changes in individuals' social ranks were frequent and followed by changes in performance on the individual learning task; a drop in an animal's relative rank was accompanied by improved performance relative to the rest of the group, and a rise by poorer performance, leading the authors to assert that there did not seem to exist an 'inherent negative relationship between some hypothetical generalized learning ability and social rank' (Bunnell & Perkins 1980, page 522).…”
Section: Discussionmentioning
confidence: 99%
“…Dominant rhesus macaques, Macaca mulatta, for example, appear to show superior learning capacities to subordinates when tested within the group, but when dominants and subordinates are separated their learning performance is similar (Drea & Wallen 1999). Being low in a dominance hierarchy may force individuals to deviate from their usual behaviour, for instance to relinquish access to resources, or conversely to learn novel acts to obtain resources, as reported in a variety of primate and avian species (e.g.…”
mentioning
confidence: 99%
“…This phenomenon highlights the importance of an ecological approach to theories of cognitive evolution and to the design of cognitive experiments. There are few experiments designed specifically to investigate the socioecology of primate social cognition (but see Drea & Wallen 1999, for an exception), and there are no agreed-upon conventions for how to maximize the ecological validity of cognitive tasks for use with chimpanzees (e.g. would being tested in a social group make a difference and should males and females be tested in the same way?).…”
Section: Discussionmentioning
confidence: 99%
“…A brain imaging study by Zink, et al (2008) found, for example, that lower social status in an unstable hierarchy activated portions of the brain associated with social anxiety, despite the fact that status was irrelevant for the outcome of the task. A study of high-and low-status rhesus monkeys by Drea and Wallen (1999) found that monkeys who had learned to perform a color discrimination task were less likely to demonstrate that knowledge when they were in a group with higher-status monkeys, despite a low incidence of aggressive behavior.…”
Section: Power Status Risk-taking and Experimentationmentioning
confidence: 99%